Struktur dan Fungsi Pantun Minangkabau dalam Masyarakat Pasa Lamo, Pulau Punjung, Dharmasraya - Fandi, Leo; Agustina, Agustina; Nurizzati, Nurizzati (Universitas Negeri Padang, 2012)
The purpose of this study is to describe and analysis the structure and the function of rhyme Pasa Lamo Minangkabau community, Pulau Punjung, Dharmasraya. The data of this study is the rhyme Minangkabau in Pasa Lamo. Source of research data is the primary source of oral sources as spoken by the informant as the original speakers. Data was collected using the methods and techniques refer to the record and advanced engineering techniques as noted. The findings of the study include three things: (1) transcription in Pasa Lamo rhyme into Indonesian, (2) the structure of rhyme in Pasa Lamo, consisting of the physical structure and inner structure, and (3) the function of rhyme in Pasa Lamo.